Changing Eruptive Styles at the South-East Crater of Mount Etna: Implications for Assessing Lava Flow Hazards - Cappello, Annalisa; Ganci, Gaetana; Bilotta, Giuseppe; Corradino, Claudia; Hérault, Alexis; Del Negro, Ciro (Frontiers in Earth Science, 2019)
The summit area of Mount Etna has undergone large morphological variations since the formation of the South-East Crater (SEC) in 1971 and New Southeast Crater (NSEC) in 2007, which have also marked a notable change in the eruptive activity of the volcano. Indeed, in less than 50 years, the SEC area has been the source of more than two hundreds of eruptions characterized by the emission of lava fountains, pyroclastic material, and short-lasting lava flows, which are the greatest hazard presented to the tourist facilities on the southern flank of Etna. Here we statistically analyze the main quantitative parameters (i.e. duration and lava volume) of 154 well-documented eruptive events occurred since 1998 with the aim of characterizing the time-volume evolution of the SEC activity. From 1998 to 2018, we find a cumulative volume of ∼135 millions of cubic meters that gives a long-term output rate of ~0.21 m3/s, with a remarkable change in the eruptive style (longer and more voluminous events) starting from 2011. Taking advantage of this analysis and lava flow simulations run on a Pléiades-derived topography updated to 2016, we also present the new hazard map from lava flow inundation in the SEC area, establishing an important basis for mitigation decisions. Our SEC hazard map covers an area of ~15 km2, with lava flows spreading both towards south-west and south-east, reaching the lowest altitude of about 1,500 m a.s.l.